2022
DOI: 10.3390/en15093020
|View full text |Cite
|
Sign up to set email alerts
|

Surface Complexation Modelling of Wettability Alteration during Carbonated Water Flooding

Abstract: CO2 capture and utilization is an effective tool in reducing greenhouse gas emissions and hence, combating global warming. In the present study, surface complexation modeling (SCM) with the geochemistry solver, PHREEQ-C, was utilized to predict the wettability alteration of minerals, sandstone reservoir rocks (SRR), and pseudo-sandstone rocks (PSR) and mineral mixtures during carbonated water (CW) injection. The bond products, which is defined as the product of the mole fraction of oppositely charged mineral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Also, the SCM technique can be used to study the trends in results from laboratory experiments and as the foremost screening tool to predict the potential wettability modification of rocks by CW. 175 Recently, Mehdiyev et al 175 employed the SCM technique with the geochemistry solver, PHREEQC, to predict the wettability modification of minerals and rocks in the presence of CW. They revealed that the wettability preference of a rock depends on the effective surface area and wetting state of the individual minerals of the rock.…”
Section: Surface Complexation Modeling (Scm)mentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the SCM technique can be used to study the trends in results from laboratory experiments and as the foremost screening tool to predict the potential wettability modification of rocks by CW. 175 Recently, Mehdiyev et al 175 employed the SCM technique with the geochemistry solver, PHREEQC, to predict the wettability modification of minerals and rocks in the presence of CW. They revealed that the wettability preference of a rock depends on the effective surface area and wetting state of the individual minerals of the rock.…”
Section: Surface Complexation Modeling (Scm)mentioning
confidence: 99%
“…Compared to other wettability identification methods (e.g., United States Bureau of Mines (USBM) and Amott–Harvey wettability test), SCM can accurately predict the dominant adhesion mechanisms (cation bridging and carboxylic oil component adsorption) that led to wetting preferences of minerals and rocks. Also, the SCM technique can be used to study the trends in results from laboratory experiments and as the foremost screening tool to predict the potential wettability modification of rocks by CW …”
Section: Modeling Of Cwimentioning
confidence: 99%
See 2 more Smart Citations
“…Lately, there has been a growing interest within the energy industry toward wettability alteration. This interest emerges not just from the need to enhance well productivity but also to explore the potential for CO 2 sequestration. , Mehdiyev et al . modeled wettability alteration during carbonated water flooding for CO 2 sequestration and utilization.…”
Section: Introductionmentioning
confidence: 99%